Splitting Finite Difference Methods on Staggered Grids for the Three-Dimensional Time-Dependent Maxwell Equations (Communications in Computational Physics, 2018)
In this paper, we study splitting numerical methods for the three-dimensionalMaxwell equations in the time domain. We propose a new kind of splitting finite-difference time-domain schemes on a staggered grid, which consists of only two stagesfor each time step. It is proved by the energy method that the splitting scheme is unconditionally stable and convergent for problems with perfectly conducting boundaryconditions. Both numerical dispersion analysis and numerical experiments are alsopresented to illustrate the efficiency of the proposed schemes.